Evaluation of Salivary and Serum Alpha Amylase Level in Dental Caries of Adolescence - Fatemeh Ahmadi- Motamayel; Mohammad Taghi Goodarzi; Zohreh Jamshidi; Ali Mahdavinezhad; Nasrin Rafieian (Brazilian Dental Science)
Objective: Some previous studies suggested a significant relationship between alpha- amylase, and caries formation. This study was implemented in order to investigate the interrelation between level of salivary and serum alpha- amylase and dental caries. Material and Methods: In this cross-sectional investigation, un-stimulated whole saliva  and serum sample was collected from 118 high school students  who were divided to four groups: Caries free female (N= 28), caries active females (N=35), caries free males(N= 28) and caries active males(N= 27). Mean levels of salivary and serum alpha-amylase was assayed by spectrophotometric method to assay enzyme kinetics. Data were analyzed using student’s t-test and chi-square test. Results: The results of this study demonstrated  that salivary and Serum alpha- amylase were  significantly   higher in caries active group as compared to carries free group(P = 0.002, P= 0.001 respectively). In addition in male groups the mean salivary and serum alpha -amylase was significantly higher in caries active as compared to caries free (P = 0.002, P = 0.02 respectively) and in   female Groups the mean serum   alpha- amylase was statistically significant higher in caries active as compared to caries free (P = 0.01). Conclusion: The results of this study demonstrated significant association between salivary and serum alpha- amylase in adolescence with dental caries. More research should be done to demonstrate real relation between   alpha amylase and   dental caries.